2012
DOI: 10.1107/s1744309112015230
|View full text |Cite
|
Sign up to set email alerts
|

The ParE2–PaaA2 toxin–antitoxin complex fromEscherichia coliO157 forms a heterodocecamer in solution and in the crystal

Abstract: Escherichia coli O157 paaR2-paaA2-parE2 constitutes a unique threecomponent toxin-antitoxin (TA) module encoding a toxin (ParE2) related to the classic parDE family but with an unrelated antitoxin called PaaA2. The complex between PaaA2 and ParE2 was purified and characterized by analytical gel filtration, dynamic light scattering and small-angle X-ray scattering. It consists of a particle with a radius of gyration of 3.95 nm and is likely to form a heterododecamer. Crystals of the ParE2-PaaA2 complex diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 58 publications
1
14
0
3
Order By: Relevance
“…Moreover, the role of PaaA2 possibly extends beyond just toxin neutralization. Recently, it has been shown that the ParE2-PaaA2 complex consists of a stable heterododecamer in solution (Sterckx et al, 2012) and that this toxin-antitoxin complex binds the promoter region of the paaR2-paaA2-parE2 module in vivo (Hallez et al, 2010). For many examples, the importance of intrinsically disordered segments in DNA-protein interactions has been recognized (Fuxreiter et al, 2011).…”
Section: Conformational Ensemble Of Paaa2mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the role of PaaA2 possibly extends beyond just toxin neutralization. Recently, it has been shown that the ParE2-PaaA2 complex consists of a stable heterododecamer in solution (Sterckx et al, 2012) and that this toxin-antitoxin complex binds the promoter region of the paaR2-paaA2-parE2 module in vivo (Hallez et al, 2010). For many examples, the importance of intrinsically disordered segments in DNA-protein interactions has been recognized (Fuxreiter et al, 2011).…”
Section: Conformational Ensemble Of Paaa2mentioning
confidence: 99%
“…The gene coding for PaaA2 was cloned and expressed in E. coli as described before (Sterckx et al, 2012). The used construct equips PaaA2 with an N-terminal FLAG tag and ParE2 with a C-terminal His tag.…”
Section: Experimental Procedures Production and Purification Of E Comentioning
confidence: 99%
See 1 more Smart Citation
“…40) observa-se uma distribuição normal ao redor do eixo y=0 com uma dispersão menor do que 20%, encontrando-se dentro do critério de aceitação do Manual de Garantia da Qualidade -MAPA. 76 O valor de t de student para a análise de regressão 83 Uma possível explicação para a presença deste pico interferente é dada por Cramer et al 97 e Sueck et al 98 , os quais tem estudado os produtos de degradação térmica da ocratoxina A. O nome químico da ocratoxina A (OTA) ou 14-(S)-ocratoxina A, de acordo com a IUPAC é N-((3R)-(5-cloro-8-hidroxi-3-metil-1-oxo-7-isocromanil) carbonila)-3-fenil-L-alanina (Figura 42). A OTA tem sido amplamente relatada em café, 28,30,31 assim como sua redução durante o processo de torra.…”
Section: Avaliação Das Figuras De Mérito Do Método In-tube Spme-uplc-unclassified
“…É uma das técnicas atuais mais importantes que provê bastante informação e permite também a detecção simultânea de outras micotoxinas presentes que não tem a propriedade de fluorescência e a detecção de micotoxinas emergentes ou metabólitos mascarados 27. Além disso, fornece baixos limites de detecção e quantificação, porém um pouco maiores do que os obtidos com HPLC-FDL.46 Os parâmetros de qualidade de um método de análise consiste em uma serie de experimentos que permitem avaliar parâmetros ou figuras de mérito com a finalidade de demonstrar que o método é adequado para a finalidade proposta 76. A avaliação dos parâmetros de validação varia de acordo com cada guia, porém os parâmetros são basicamente os mesmos.…”
unclassified